The effect of non-uniform bending on the lateral stability of steel beams with slender cross-section at elevated temperatures. (15th May 2018) - Couto, Carlos; Maia, Élio; Vila Real, Paulo; Lopes, Nuno
Highlights: LTB of steel beams with slender cross-sections and non-uniform bending in fire. Non-uniform bending has a beneficial effect on LTB. Proposal to consider this beneficial effect by using factor " f ". Around 20, 000 GMNIA simulations demonstrate the accuracy and validity of proposal. Abstract: In this paper, the effect of non-uniform bending on the lateral torsional buckling (LTB) of steel beams with slender cross-sections subjected to elevated temperatures is numerically investigated. Local buckling is the main failure mode for slender sections whereas the lateral torsional buckling is one of the principal failure modes for beams, thus the interaction between these two failure modes greatly affects the load-bearing capacity of the beams. In the case of fire, recent studies have shown that the design procedures of Part 1–2 of Eurocode 3 are unreliable and too conservative due to the inconsistent treatment of such interaction phenomena. On the other hand, it is known that non-uniform bending has a beneficial effect on the ultimate capacity of beams but there is limited knowledge about its influence on beams with slender cross-sections. This work aims at studying the influence of non-uniform bending on the combined local-global interaction response of beams with slender open I-sections in the case of fire. The inclusion of the factor " f " in a recently proposed LTB design procedure that groups the response of the beams into different ranges of effective section factors is analysed and the accuracy of such proposal is demonstrated against around 20, 000 GMNIA (Geometrically and Material Non-Linear Analyses with Imperfections) simulations. Finally, the improvements of this proposal on the current Eurocode 3 design procedure are highlighted.